Bacterial meningitis as a cause of death in lung transplant donors: Early outcomes in recipients. Issue 8 (25th June 2018) - Grewal, Harpreet S.; Highland, Kristin B.; McCurry, Kenneth; Akindipe, Olufemi; Budev, Marie; Mehta, Atul C.
Abstract: Background: Lung transplant remains an established treatment for end‐stage lung disease, but limited organ availability remains a major barrier and contributor to waitlist mortality.1 Only 20% of available organs are considered suitable for lung transplantation (Am J Transplant, 16, 2016 and 141; Thorac Surg Clin, 25, 2015 and 35). Successful lung transplantation has been reported from donors infected with bacterial or fungal organisms, but there is a paucity of evidence regarding the use of donors with bacterial meningitis (Transplant Proc, 32, 2000 and 75; Transplantation, 64, 1997 and 365; Ann Thorac Surg, 86, 2008 and 1554). Method: The Cleveland Clinic lung transplant database was retrospectively reviewed for patients between January 1998 and December 2014. Post‐transplantation outcomes collected included graft dysfunction, infectious complications, and survival. Results: The recipients were identified as having lungs from donors with bacterial meningitis. All recipients remained free of infectious organisms responsible for bacterial meningitis related in the donor. Severe primary graft dysfunction (PGD) was not seen in these recipients. Conclusion: In our study, lung transplantation from increased risk donors with bacterial meningitis was not associated with an increased risk of early infectious complications in recipients. Donors with bacterial meningitis should be considered for lung donation and may expand the donor pool safely.